Fluid mechanics - Streeter Vicror L. (McGraw - Hill book company, 1958)
Books about liquid handling are analyzed through chapters. The chapter on dimensional analysis has been consolidated and moved to Chapter 4 for more emphasis. The chapter on fluid statics has been slightly shortened, and dealing with viscous effects, Chapter 5, has been shortened, with examples and compression applications moved to Chapter 6.